Endometrial hyperplasia and progesterone resistance: a complex relationship - Mekan R. Orazov; Ludmila M. Mikhaleva; Irina A. Mullina (RUDN Journal of Medicine, 2023)
The endometrium is one of the most dynamic tissues that constantly undergoes changes during the menstrual cycle in women of the reproductive period. All these processes take place mainly under the influence of steroid hormones that are produced in the woman’s body. However, it is important to remember that throughout life the endometrial tissue undergoes changes under the influence of various factors that lead to imbalances in hormonal regulation. All these changes can lead to the development of endometrial hyperplasia, which has a high risk of both recurrence and malignization. Over the past few decades, the incidence of endometrial cancer has increased in many countries. This trend is thought to be related to the increasing prevalence of obesity, as well as to changing female reproductive patterns. Although there are currently no well-established screening programmers for endometrial cancer, endometrial hyperplasia is a recognized precursor, and its detection provides an opportunity for prevention. Studying the pathogenesis and risk factors will give a great advantage in the future to prevent possible complications. At this point, the activity and inhibition of the different hormone isoforms can lead to different hyperplastic processes. The management of patients depends on many factors: age, species, reproductive potential and other factors. Therefore, a comprehensive approach to treatment is always necessary. In recent years, interest in the study of endometrial hyperplasia has increased dramatically due to the increase in endometrial cancer. Therefore, the issue of early diagnosis and prevention is most urgent in modern gynecology and requires further study. This review reflects the current understanding of the disruption of progesterone signaling mechanisms in endometrial hyperplasia according to domestic and foreign literature.